Topology of fiber bundles - Zhang, Hainan (Kansas State University, 2014)
This report introduces the fiber bundles. It includes the definitions of fiber bundles such as vector bundles and principal bundles, with some interesting examples. Reduction of the structure groups, and covering homotopy theorem and some specific computation using obstruction classes, Cech cohomology, Stiefel-Whitney classes, and first Chern classes are included.
Keywords: Introduction to Fiber Bundles; obstruction theory from characteristic class; 1st SW class and 1st Chern class; Mathematics (0405)